The epidemiology and health burden of neurocysticercosis in tertiary hospital of Nepal - Sah, RB; Subedi, L; Pandey, N; Sah, BP; Jha, S; Shah, U; Jha, N; Pokharel, PK (Journal of Chitwan Medical College, 2014)
Neurocysticercosis (NCC) is the most common parasitic infestation of the central nervous system and is one of the major public health problems in developing nations like Nepal. This study was conducted to find out total number of neurocysticercosis cases in BPKIHS from 2005 to 2013 AD and to know the duration for which cases were admitted and improvement seen in them. This is a hospital based retrospective study conducted from 31st March to 13th April 2014 to see the number of NCC in B P Koirala Institute of Health Sciences, Dharan of Nepal, a tertiary level referral hospital in the Eastern Nepal. It was study in which secondary data, consistent with the diagnosis of Neurocysticercosis was collected from the Medical Record Section of BPKIHS and reviewed. One hundred fourteen cases of neurocysticercosis were enrolled. The patients were predominantly males (nearly 63.2%) and it was more commonly seen in 2-20 years age group (42%). Most of the cases were from Sunsari District. Most of the patients (63.2%) were admitted in Medicine wards. Almost 90.4% of admitted Neurocysticercosis cases were improved in BPKIHS. The trend of Neurocysticercosis cases did not show any showed any consistent pattern in the past nine years. We conclude that the problem of Neurocysticercosis is common and has become a key public health concern for all. DOI: http://dx.doi.org/10.3126/jcmc.v4i2.10854 Journal of Chitwan Medical College 2014; 4(2): 13-16